2014
DOI: 10.1002/brb3.290
|View full text |Cite
|
Sign up to set email alerts
|

Neural adaptation to silence in the human auditory cortex: a magnetoencephalographic study

Abstract: IntroductionPrevious studies demonstrated that a decrement in the N1m response, a major deflection in the auditory evoked response, with sound repetition was mainly caused by bottom-up driven neural refractory periods following brain activation due to sound stimulations. However, it currently remains unknown whether this decrement occurs with a repetition of silences, which do not induce refractoriness.MethodsIn the present study, we investigated decrements in N1m responses elicited by five repetitive silences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Previous research has shown that transient responses to the onset of an acoustic stimulus are exhibited by some neurons in the auditory cortex of rats [52, 53] and humans [54, 55]. If similar response patterns are present in our ECoG data, we can expect the performance of our phoneme likelihood estimator to vary throughout the duration any given utterance.…”
Section: Resultsmentioning
confidence: 80%
“…Previous research has shown that transient responses to the onset of an acoustic stimulus are exhibited by some neurons in the auditory cortex of rats [52, 53] and humans [54, 55]. If similar response patterns are present in our ECoG data, we can expect the performance of our phoneme likelihood estimator to vary throughout the duration any given utterance.…”
Section: Resultsmentioning
confidence: 80%
“…Studies on auditory information processing have also shown that when auditory stimuli were presented precedingly, the amplitude of the N1 component induced by the first sound stimulus was the largest, and the N1 induced by the subsequent sound stimulus was significantly reduced (Budd et al., 1998; Okamoto & Kakigi, 2014). In the present study, we found the effect of RS on the SiFI.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were asked to stay in a relaxed waking state during the measurement, and not to pay attention to the sound stimuli. To control for confounding changes in attention and vigilance, subjects watched a soundless movie of their choice (Fujioka et al, 2006; Boh et al, 2011; Okamoto and Kakigi, 2014). Alertness and compliance were verified by video monitoring.…”
Section: Methodsmentioning
confidence: 99%